Barriers to obtaining employment for people with severe mental illness experiencing homelessness. (August 2014) - Poremski, Daniel; Whitley, Rob; Latimer, Eric
Abstract Background: The rate of unemployment among homeless people is estimated to exceed 80%. A high prevalence of mental illness partially explains this figure, but few studies about the relationship between employment and homelessness have focused on homeless people with mental illness. Aim: The present study explores the self-reported barriers to employment in a sample of individuals with mental illness when they were homeless. Methods: A sample of 27 individuals with mental illness and recent experiences of homelessness, who had expressed an interest in working, participated in semi-structured qualitative interviews. Inductive analysis was used to identify barriers to employment. Findings: The prominent barriers include: (1) current substance abuse, (2) having a criminal record, (3) work-impeding shelter practices, and (4) difficulties obtaining adequate psychiatric care. Conclusion: Individuals who have been homeless and have a mental illness report facing specific barriers associated with mental illness, homelessness, or the interaction between the two. Additional research should explore how supported housing and employment interventions can be tailored to effectively serve this group.